2006
DOI: 10.1002/adma.200500202
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Synthesis and Growth Model of Amorphous Silicon Nanotubes with Periodically Dome‐Shaped Interiors

Abstract: strate rotation, x sub , was related to the deposition rate, r, and the pitch of the film, p, as follows: p = r/x sub . Deposition rates were in the range 5-15 Å s -1 . Samples on both the silicon and glass substrates were cleaved using a diamond scribe prior to SEM imaging.Transmission Ellipsometry: A variable-angle spectroscopic ellipsometer (VASE, J. A. Woollam, Inc.) used in transmission mode was used to measure the transmission of p-and s-polarized light through the samples deposited on glass, and also to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Controllable syntheses of SiO 2 nanotubes with dome shaped interiors have been prepared by pyrolysis of silanes over Au catalysts. 282 High aspect-ratio, self-organized nanotubes of TiO 2 are obtained by anodization of titanium. 283 These self-organized porous structures consist of pore arrays with a uniform pore diameter of ∼100 nm and an average spacing of 150 nm.…”
Section: Inorganic Nanotubesmentioning
confidence: 99%
“…Controllable syntheses of SiO 2 nanotubes with dome shaped interiors have been prepared by pyrolysis of silanes over Au catalysts. 282 High aspect-ratio, self-organized nanotubes of TiO 2 are obtained by anodization of titanium. 283 These self-organized porous structures consist of pore arrays with a uniform pore diameter of ∼100 nm and an average spacing of 150 nm.…”
Section: Inorganic Nanotubesmentioning
confidence: 99%
“…Metallic (armchair) and semiconductor (zigzag and mixed) characteristics of SiNTs have been demonstrated by first-principle calculations [79]; and metallic single-walled SiNTs were reported, using ab initio calculations [76]. Although some papers have been published on the preparation of the SiNTs by other methods [80][81][82][83][84][85][86][87][88], there are few papers in which the arc discharge method was adopted. But as a whole, it seems that the studies on the SiNTs may be developed rapidly in the coming years (the number of literatures in the online database of SCI in last five years is about half of the total literatures since 2000).…”
Section: Si Nanotubesmentioning
confidence: 99%
“…Recently, there has been a rapid growth research interests in advanced nanotechnology which gives great promise for achieving new sensing materials including high performance nanomaterials [6] and nanoscale eletronics devices [7]. Silicon, as the same group element with carbon in the periodic table of elements has similar structure with carbon, and [8], template combined CVD [9]. In terms of theory, Luo et al [10] studied the structures and electronic properties of pure (5,5) and (5,0) SiNTs with the first principles of density functional method, and found that the conductivity of SiNTs was connected with the chirality of its structure.…”
Section: Introductionmentioning
confidence: 99%